Pengaruh Ukuran Partikel Jagung dan Diameter Die Ransum Bentuk Pelet pada Kualitas Fisik dan Performa Tikus Putih (Rattus norvegicus) - Heri Ahmad Sukria; Heru Nugraha; Anuraga Jayanegara (Jurnal Ilmu Pertanian Indonesia, 2020)
This study was conducted to evaluate physical properties and nutritive values of white rats (Rattus norvegicus) diets using different screen sizes of ground corn and different die sizes of the pellet. The experiment was divided into two trials. The first experiment aimed to find the effect of different particles of corn and die sizes of pellet on the physical properties and quality of white rat diet. The experiment consisted of 4 treatments and 4 replications namely, P1 (screen 3 mm and die 4 mm), P2 (screen 3 mm and die 16 mm), P3 (screen 5 mm and die 4 mm), and P4 (screen 5 mm and die 16 mm). The parameters measured were Pellet Durability Index (PDI), Specific density, Loose Bulk Density, and compacted Bulk Density of the pelleted diet. The second experiment was feeding trial to measure the performance of the white rats fed the pelleted diets. A total number of 20 white rats were used and divided into four treatments of the first experiment and replicated 5 times. The parameter measured were feed intake, final body weight, as well as the digestibility of dry matter and organic matter. Result of the experiments showed that the pellet durability index was significantly affected by the particle size of corn and the diameter of the pellet (P<0.01). In the feeding trial, the rats fed pelleted with the die of 16 mm resulted the highest feed intake (P<0.05). The P1 diet resulted the best physical pellet quality whereas P2 resulted the best performance of the experimental rats fed the pelleted diet. It can be concluded that to produce the best pelleted diet of rat, the ingredients should be ground with 3 mm screen size and the pellet was produced with the die diameter of 16 mm. Keywords: die diameter, particle size, pellet durability index, pellet physical quality, white rats